A Comparative Study on Fatigue Resistance Between Cobalt-Chromium and Nickel-Chromium Occlusal Rest - Rahman, Asheque; Choudhury, Marium; Yazdi , Kazi Shagufa; Shamsuzzaman, Mohammad (Journal of Dhaka National Medical College & Hospital, 2022)
Background: Fatigue failure in a removable cast partial denture framework includes fracture of the occlusal rest at the rest-minor connector angle. Objective: To evaluate the fatigue resistance of 0.7mm-thick occlusal rests casted with Cobalt-Chromium (Co-Cr) and Nickel-Chromium (Ni-Cr) alloy. Materials and Method: It was a comparative observational in vitro study was carried out in the Department of Prosthodontics, Faculty of Dentistry, Bangabandhu Sheikh Mujib Medical University & Material & Metallurgy Department, Bangladesh University of Engineering & Technology (BUET). The study was carried out during the period of January 2006 to December 2007. Total 70 casted metals with no porosity, no cracks and metal thickness 0.7 mm were included. This divided into two groups, Group-A consisted of 35 occlusal rest casted with Ni-Cr alloy and Group-B consisted of 35 occlusal rest casted with Co-Cr alloy. The specimen consisted of occlusal rest (0.7x2.0x10 mm), vertical minor connector (0.9x2.0x5.0 mm), and denture base connector (1.5x5.0x25 mm). Thirty-five specimens of each group were casted with Co-Cr and Ni-Cr alloy. Five specimens from each group were subjected to a load-deflection test conducted to determine the amount of deflection to be used in fatigue test. The fatigue test was performed such that the occlusal rest component was deflected by displacing the denture base component in a tissue ward direction. Predetermined denture base displacement values of 0.25 and 0.49 mm were applied for Co-Cr and Ni-Cr alloy specimens respectively, and repeated at a rate of 500 cycles/min by use of a displacement-controlled fatigue-testing machine, until occlusal rest failure occurred or a preset limit of 2 million cycles was achieved. The survival rates of the occlusal rests were calculated assuming a chewing cycle of 2x102 per year. All data of the study were collected and recorded in specific parameters of fatigue resistance and survival rate of occlusal rest. Data were analyzed by using computer based programmed statistical package for social science (SPSS) for windows version 15. Student's t-test was done to find out the statistical significance. P-value <0.05 was considered as significant. Results: The mean fatigue resistance of Co-Cr alloy was 1559066 cycle, Ni-Cr alloy was 383300 cycles. The mean load deflection of Co-Cr alloy was 0.25mm; Ni-Cr alloy was 0.49mm. Conclusions: Co-Cr occlusal rest is more rigid and resistant to fatigue than Ni-Cr occlusal rest. J. Dhaka National Med. Coll. Hos. 2022; 28 (02): 23-27